HERCULES: Haptically-Enabled Remotely Controlled Ultrasound Examination System - Parham M. Kebria; Saeid Nahavandi; Numan Kutaiba; Niki Koutrouza; Natalie Yang; Hamed Asadi; Glenn Guest (IEEE Access)
The main purpose of the study is to investigate and demonstrate the feasibility and practicality of using a haptically-enabled remotely controlled ultrasound examination system (HERCULES) to perform point-of-care ultrasound. Robotic ultrasound is an emerging and important technology. This technology can help in performing ultrasound imaging in potentially contagious patients while minimizing risks of infections for sonographers (persons who perform ultrasound). This study assesses whether the robotic ultrasound system can reduce the musculoskeletal injuries sonographers endure. We developed a haptically-enabled robotic ultrasound system, which provides sonographers with a sense of touch throughout the scan. The system has haptic capabilities in which the sonographer can feel the contact force remotely and would be able to apply pressure appropriately to safeguard the patient. The system is equipped with various force thresholds. The sonographer can view the patient as well as the transducer’s position and orientation. More than 500 robotic images were captured, and a supplementary evaluation by expert radiologists was conducted to provide initial insights into image quality. In total, 56 subjects, 31 female and 25 male, aged from 21 to 55 years, participated in the clinical trials. An assessment is also carried out on the stimulation of the sonographer’s muscles during conventional vs. robotic scanning. As a result, the sonographer experienced substantial relief in back and neck muscles, right abductor pollicis brevis and right C4 paraspinal, by 88.12%, 89.19%, 93.57%, 82.0%, 72.83%, and 75.1% reduction from manual to teleoperated scenario, respectively. Subjects also reported a much more comfortable experience during robotic ultrasound scans.